Pembuatan robot pelontar bola tenis meja low budget untuk meningkatkan kompetensi atlet tenis meja di kabupaten blora - Yudha, Fitroh Anugrah Kusuma; Bambang Riyanta; Jurit Tri Susetyorini (Program Studi Akuntansi IKOPIN, 2022)
Many people practice the sport of table tennis, with a manual like practicing one-on-one. This method is said to be less effective because it drains the energy of a coach who trains his players, also the strokes from a table tennis coach will decrease in accuracy if he is training for a long period of time. The table tennis branch under the auspices of PTMSI Blora Regency still has several problems including in the facilities and infrastructure for training athletes independently using table tennis ball throwing robot media, as well as how to make ball throwing robots that require a small fee. The first solution to the problem is to make a simple table tennis ball throwing robot with a minimum cost of under 1.5 million, for the second solution, training is held to make a ball throwing robot. The development of science in the efficiency of table tennis practice can use tools such as table tennis ball throwing robots, to make a robot that can produce adjustable speed and spin shots having several procedural steps to achieve the desired results such as the process of finding the required information, testing try, and implementation. The result that is expected to be achieved is to produce a table tennis ball throwing robot with the speed, period, and spin of the shot that can be adjusted via a potentiometer. There are two types of spin, namely topspin, and backspin, and can throw 30-80 balls.